Strategy for Developing a Historical Tourism Object of Soekarno's Exile House as a Means of Student Character Education in Ende Regency - Natsir B. Kotten; Korosando, Fransiskus; Bede, Elias (International Journal of Educational Research Excellence (IJERE), 2023)
The aim of this research is to reveal: (1) the development strategy carried out by the Ende Regency Education and Culture Office to develop the potential of the historical tourist attraction of Soekarno's exile as a means of character education for students in Ende, (2) the level of student response in visiting the historical tourist attraction of Soekarno's exile in Ende. Ende Regency, and (3) character values that are role models for students towards the historical tourist attraction of the Soekarno Exile House in Ende. This research uses a qualitative approach. The research location is at the Soekarno Ende exile house site. The informants in this research were the head of the education and culture service, the head of the culture and tourism service, teachers and students, as well as the visiting community. Data collection techniques use (1) interviews, (2) observations, and (3) documentation studies. Data analysis was carried out using three flows , namely data reduction, data display, and conclusion drawing/verification. The results of the research show that: (1) The strategy for developing Soekarno's House of Exile includes: conducting outreach to the wider community through print and electronic media, a museum love program shown to students through outreach to school principals, and collaboration between the Department of Education and Culture to PPKn and history teachers, (2) The strategy for developing Soekarno's house of exile received a positive response from students, and (3) The character values that students exemplify towards the historical tourist attraction of Soekarno's house of exile, curiosity, responsibility, national spirit, and love of the homeland.